1993
DOI: 10.1038/bjc.1993.295
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous cortisol exerts antiemetic effect similar to that of exogenous corticosteroids

Abstract: Summary Lower pre-chemotherapy night time cortisol excretion predicted more severe cisplatin induced nausea and vomiting in 42 ovarian cancer patients receiving ondansetron as a single antiemetic agent. Dexamethasone administration added to the antiemetic effect of ondansetron principally in patients who had low excretion of cortisol.Corticosteroids as single antiemetic agents have a well documented effect on mild to moderate chemotherapy induced emesis (Cassileth et al., 1983). During highly emetogenic chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
22
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 10 publications
(13 reference statements)
4
22
0
Order By: Relevance
“…Corticoid metabolism is probably also involved in the pathophysiology of chemotherapy-induced emesis. Corticosteroids have shown a remarkable anti-emetic efficacy and a relationship between anti-emetic efficacy of corticosteroids and lower basal cortisol excretion has been reported (Hursti et al, 1993). The present data in carboplatin-treated female patients confirm these findings and indicate a close relationship between cortisol excretion levels and the risk of emesis.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Corticoid metabolism is probably also involved in the pathophysiology of chemotherapy-induced emesis. Corticosteroids have shown a remarkable anti-emetic efficacy and a relationship between anti-emetic efficacy of corticosteroids and lower basal cortisol excretion has been reported (Hursti et al, 1993). The present data in carboplatin-treated female patients confirm these findings and indicate a close relationship between cortisol excretion levels and the risk of emesis.…”
Section: Discussionsupporting
confidence: 81%
“…The first group contains the type of cytostatics used, the combination of different drugs and the chemotherapy dose. The second group contains gender, age, history of alcohol intake, susceptibility for motion sickness, chemotherapy experience and biochemically measurable parameters such as noradrenaline (Fredrickson et al, 1994) and cortisol (Fredrickson et al, 1992;Hursti et al, 1993). However, methodological problems of the latter studies make it difficult to draw final conclusions regarding the relation between cortisol metabolism and emesis.…”
mentioning
confidence: 99%
“…Recent research showed that nausea associated with chemotherapy is correlated with a reduction of plasma cortisol levels in cancer patients, which indicates an effect (direct or indirect) on the hypothalamic-pituitary-adrenal axis (Hursti et al, 1993;Morrow et al, 2002a). Studies in rat show elevated plasma cortisol levels with the production of CFA (Smotherman, 1985).…”
Section: Direct Action Of Stimuli On the Brain?mentioning
confidence: 99%
“…Earlier studies have mainly investigated different corticosteroid quantities in comparison with no or placebo medication. Prior work in this area suggests that especially patients with low prechemotherapy night-time cortisol excretion profit from cortisol administration (Fredrickson et al, 1992), that endogenous cortisol exerts antiemetic effects similar to that of exogenous corticosteroids (Hursti et al, 1993), and dexamethasone in high doses (20 mg) may impair the control of delayed symptoms (Peterson et al, 1996) whereas this adverse effect was not observed at doses of 8 mg (Carmichael et al, 1994).…”
mentioning
confidence: 98%